Experimental characterization of Alfvén modes in a field-reversed configuration plasma. (29th June 2018) - Magee, R.M.; Roche, T.; Thompson, M.C.; Tobin, M.; Beall, M.; Deng, B.H.; Korepanov, S.
Abstract: High power neutral beam injection into the C-2U advanced field-reversed configuration (FRC) stimulates at least three distinct energetic particle modes, none of which have been linked to a performance limitation. Here we present an experimental characterization of one mode in particular, a high frequency mode ( ) observed in the decaying phase of the FRC. The mode is reminiscent of the compressional Alfvén eigenmodes observed in spherical tokamaks: its frequency scales with the edge Alfvén velocity and it co-propagates with injected beam ions perpendicular to the magnetic field. There are multiple pieces of evidence that the mode resides outside of the FRC and therefore likely has little to no effect on the confinement properties of the FRC itself.